The Podovirus ϕ80-18 Targets the Pathogenic American Biotype 1B Strains of Yersinia enterocolitica - Filik, Karolina; Szermer-Olearnik, Bożena; Wernecki, Maciej; Happonen, Lotta J.; Pajunen, Maria I.; Nawaz, Ayesha; Qasim, Muhammad Suleman; Jun, Jin Woo; Mattinen, Laura; Skurnik, Mikael; Brzozowska, Ewa (Frontiers in Microbiology, 2020)
We report here the complete genome sequence and characterization of Yersinia bacteriophage vB_YenP_80-18. 80-18 was isolated in 1991 using a Y. enterocolitica serotype O:8 strain 8081 as a host from a sewage sample in Turku, Finland, and based on its morphological and genomic features is classified as a podovirus . The genome is 42 kb in size and has 325 bp direct terminal repeats characteristic for podoviruses. The genome contains 57 predicted genes, all encoded in the forward strand, of which 29 showed no similarity to any known genes. Phage particle proteome analysis identified altogether 24 phage particle-associated proteins (PPAPs) including those identified as structural proteins such as major capsid, scaffolding and tail component proteins. In addition, also the DNA helicase, DNA ligase, DNA polymerase, 5’-exonuclease, and the lytic glycolase proteins were identified as PPAPs, suggesting that they might be injected together with the phage genome into the host cell to facilitate the take-over of the host metabolism. The phage-encoded RNA-polymerase and DNA-primase were not among the PPAPs. Promoter search predicted the presence of four phage and eleven host RNA polymerase –specific promoters in the genome, suggesting that early transcription of the phage is host RNA-polymerase dependent and that the phage RNA polymerase takes over later. The phage tolerates pH values between 2 and 12, and is stable at 50 °C but is inactivated at 60 °C. It grows slowly with a 50 min latent period and has apparently a low burst size. Electron microscopy revealed that the phage has a head diameter of about 60 nm, and a short tail of 20 nm. Whole-genome phylogenetic analysis confirmed that 80-18 belongs to the Autographivirinae subfamily of the Podoviridae family, that it is 93.2 % identical to Yersinia phage fHe-Yen3-01. Host range analysis showed that 80-18 can infect in addition to Y. enterocolitica serotype O:8 strains also strains of serotypes O:4, O:4,32, O:20 and O:21, the latter ones representing similar to Y. enterocolitica serotype O:8, the American pathogenic biotype 1B strains. In conclusion, the phage 80-18 is a promising candidate for the biocontrol of the American biotype 1B Y. enterocolitica.